(untitled) (Bioagro, 2024)
The objective of the research was to evaluate the effect of native arbuscular mycorrhizal fungi (AMF) and organic fertilizers on the vegetative growth of cinchona (C. officinalis) under greenhouse conditions. The study was carried out using a 4A x 3B factorial arrangement (A: mycorrhizal fungus; B: organic fertilizers), which resulted in 12 treatments. The AMF were collected in Leymebamba, San Jerónimo and Conila districts, in the Amazon region, and were multiplied in the nursery in corn trap crops for 80 days. At the same time, the germination of cinchona seeds was carried out for a period of 60 days. The seedlings were transplanted and inoculated with 40 g of AMF and 40 g of organic fertilizer in 1 L containers. The LEY-GALL consortium produced the highest response per plant in height (11.53 cm) and root dry matter (79.93 mg), the LEY-HUM highest in the number (45) and length of roots (18.68 cm ), and in root dry matter (75.83 mg), the SJ-HUM highest in foliar dry matter (317.8 g), and the SJ-GALL highest in leaf area (85.83 cm2), all with statistical superiority over the rest, or the majority of consortia. The plants with the SMA-SA consortium (without mycorrhiza and without fertilizer) showed the lowest values ​​in all the variables It is concluded that the combination of native AMF with organic fertilizers favors the vegetative growth of cinchona in greenhouse conditions.